Very severe immune thrombocytopenia following SARS-CoV-2 vaccination requiring splenectomy: a case report - Marc Weiner; Robert Rodriguez-Vigouroux; Stavroula Masouridi-Levrat; Kaveh Samii (Thrombosis Journal, 2022)
Abstract Background Some conventional vaccines have been recognized as a cause of secondary immune thrombocytopenia (ITP). According to recent publications, mRNA vaccines are probably associated with an increased risk of ITP. Case presentation Our patient developed severe ITP one week after the second dose of COVID-19 mRNA vaccine. Medical management was not effective, requiring splenectomy to obtain sustained remission. Conclusion Considering the temporality and immunological hypothesis, we consider the vaccine to be the trigger of this ITP. To our knowledge, our case is, to date, the most severe case of ITP reported following SARS-CoV-2 vaccination and could help for the therapeutic management of similar patients.